Fraktal Geometri sebagai Sumber Ide Perancangan Interior Mental Healthcare Clinic di Yogyakarta - Ramadhanty, Nurina; Budiwiyanto, Joko (Institut Seni Indoensia Surakarta, 2023)
Interior Design Mental Healthcare Clinic in Yogyakarta is a facility designed as a mental health service, especially to overcome stress disorders, depression, schizophrenia, and addictive substance use disorders. This Mental Healthcare Clinic is in the form of an outpatient clinic that provides diagnosis, therapy, and prevention services for mental health disorders carried out by the disciplines of psychiatry, psychology, and social work. This design aims to design the interior of the Mental Healthcare Clinic as a facility for people with mental health disorders that is safe, comfortable and informative, and applies the theme of geometric fractal patterns in a contemporary style. The design method used includes the input, synthesis and output stages. Design results in the form of Interior Design for Mental Healthcare Clinic which has lobby facilities, multipurpose room, café, consul room, fitness therapy room, children's speech therapy room, child sensory integration therapy room, art therapy room, pharmacy, and management office